2022
DOI: 10.3390/diagnostics12030764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Fetal MRI in the Brain

Abstract: Fetal magnetic resonance imaging (MRI) has become a widely used tool in clinical practice, providing increased accuracy in prenatal diagnoses of congenital abnormalities of the brain, allowing for more accurate prenatal counseling, optimization of perinatal management, and in some cases fetal intervention. In this article, a brief description of how fetal ultrasound (US) and fetal MRI are used in clinical practice will be followed by an overview of the most common reasons for referral for fetal MRI of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…For both eCSF and ventricle volumes, we report high variance during the fetal phase followed by a notable drop in variability in the postnatal phase, reflecting many investigations (Andescavage et al, 2016b;Kyriakopoulou et al, 2017;Story et al, 2021). We also showed that relative eCSF volumes largely decrease after birth, which is a widely published radiological observation (Gholipour et al, 2017;Li et al, 2019;Dubois et al, 2021;Nagaraj and Kline-Fath, 2022)(Figures 1 and 7). This is corroborated in Lefèvre et al (2016) where the ratios of eCSF and ventricle volumes are higher in fetuses compared to premature postnatal subjects of the same age.…”
Section: Discontinuity Of Gyrification Ecsf and Ventricles Volumessupporting
confidence: 85%
“…For both eCSF and ventricle volumes, we report high variance during the fetal phase followed by a notable drop in variability in the postnatal phase, reflecting many investigations (Andescavage et al, 2016b;Kyriakopoulou et al, 2017;Story et al, 2021). We also showed that relative eCSF volumes largely decrease after birth, which is a widely published radiological observation (Gholipour et al, 2017;Li et al, 2019;Dubois et al, 2021;Nagaraj and Kline-Fath, 2022)(Figures 1 and 7). This is corroborated in Lefèvre et al (2016) where the ratios of eCSF and ventricle volumes are higher in fetuses compared to premature postnatal subjects of the same age.…”
Section: Discontinuity Of Gyrification Ecsf and Ventricles Volumessupporting
confidence: 85%
“…As a result, fetal MRI is emerging as an essential imaging modality in evaluating complex fetal abnormalities and is even outperforming US in detecting many fetal pathologies [17][18][19][20]. The more accurate diagnoses from MRI, in turn, allow for better planning during the pregnancy for the postnatal and neonatal periods and even allow for possible fetal surgery where necessary [14,21]. MRI can also be used shortly before delivery for pelvimetric measurements to assess whether an attempt at vaginal delivery is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Because the cerebellum is located in the posterior cranial fossa and is surrounded by dense petrous ridges and the occipital bone, it can withstand extrinsic pressure deformation better than the parietal bones [5] . Because ultrasound can easily visualise the foetal cerebellum, imaging the posterior fossa is becoming an integral part of many routine foetal sonograms [9] Several authors working on transverse cerebellar diameter (TCD) have found it to be a better marker for GA estimation than other clinical and biometric parameters [10,11,12] . The current study attempted to evaluate foetal cerebellar development ultrasonographically, which aids in determining foetal gestational age.…”
mentioning
confidence: 99%